2002
DOI: 10.1055/s-2002-35089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methylprednisolone on the Viability of Experimental Flow-Through Venous Flaps

Abstract: In this study, the effects of a corticosteroid, methylprednisolone, on the survival of flow-through venous flaps were investigated in rabbits. Flow-through venous flaps, sized 3.0 x 4.5 cm, were raised in the rabbit-ear model. Animals were randomly distributed into three groups, and 30 flaps were raised as follows: Group 1 (n=10): control flow-through venous flaps (intramuscular saline injection 2 ml/d); Group 2 (n=10): flow-through venous flaps with daily intramuscular methylprednisolone injection (30 mg/kg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A few experimental studies have reported increasing the survival area of FTVFs with surgical delay and intramuscularly used methylprednizolone. 1,15 Ueda et al 1 performed a de-layed procedure in flow-through venous flaps in rabbit ears. They showed a distinct increase of the survival area in delayed flaps, and this effect increased with the delay period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few experimental studies have reported increasing the survival area of FTVFs with surgical delay and intramuscularly used methylprednizolone. 1,15 Ueda et al 1 performed a de-layed procedure in flow-through venous flaps in rabbit ears. They showed a distinct increase of the survival area in delayed flaps, and this effect increased with the delay period.…”
Section: Discussionmentioning
confidence: 99%
“…They showed a distinct increase of the survival area in delayed flaps, and this effect increased with the delay period. Saray et al 15 reported the beneficial effects of systematically given methylprednizolone on the survival of flow-through venous flaps in rabbits. In his clinical study Nishi 16 reported that the rate of survival of this type of flap can be increased, if the number of anastomosed veins is increased.…”
Section: Discussionmentioning
confidence: 99%